Parametrization of the effective potential in sodium clusters - Kotsos, B. A.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
The effective radial electronic potentials for neutral sodium clusters determined by the local density approximation and the jellium model are parametrized by means οf (symmetrized) Woods-Saxon and "Wine-Bottle" symmetrized Woods-Saxon potentials. The potential parameters are deter mined by various least-squares fitting procedures. Particular attention is paid to the dependence of the radius parameter R on the particle number Ν and it is realized that for relatively smaller values of N, complex expressions of R as a function of N, are more appropriate than the standard one R = r_0N^{1/3}. It is also found that improved results in these cases are obtained with an expression, of the form R = r_0N^{1/3} + 6, which is still very simple.